VIDEO SURVEILLANCE CAMERA RECORDS AS EVIDENCE IN CRIMINAL PROCEEDINGS - case-law of the Supreme (Cassation) Court - Pisarić, Milana (Glasnik Advokatske komore Vojvodine, 2025)
/
Keywords: criminal procedure; evidence; video records; video surveillance